Finance and Development, June 2003. - International Monetary Fund. External Relations Dept. (Washington, D.C. : International Monetary Fund, 2003)
This paper describes the importance of luck, timing, and political institutions in beating inflation. The paper highlights that countries experiencing high inflation typically make several disinflation attempts, some of which succeed only temporarily. If a country trying to stabilize prices and wages is unlucky enough to be exposed to severe external shocks-for example, a decline in demand for its exports-during its disinflation, the likelihood of failure is increased. A shock such as an increase in U.S. interest rates makes failure more likely for a country with an open capital account.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet